RANCANG BANGUN BRACKET MOTOR STARTER PADA MESIN DIESEL JETMAN R175D - Purwono, M. Anggie Mulyo; Gamayel, Adhes; Zaenudin, Mohamad; Saleh, YKP (Politeknik Negeri Sriwijaya, Indonesia, 2024)
The starter system is a component that serves to start or run an engine. Usually, the starter system on the single-cylinder engine is a conventional starter, which is still done manually by an operator. Modification activities in the form of adding an electric starter system have been carried out in this study. The focus of the study was carried out on the design of the brackets of the electric starter system. Bracket is a support plate component used as a stand for the starter motor system. In this design, 3 types of bracket models (Model 1, 2, 3) starter motors are designed with simulation testing and vibration tests on each bracket model. Simulation testing with the finite element method to determine the deflection value (deformation) and fatigue (equivalent stress) in the material used. Vibational testing is carried out to obtain design results that are able to withstand vibrations that occur in single-cylinder engines. Based on the simulation results, the bracket model ( Model 1) with a maximum value of total deformation of 0.00012047 mm with a load of 6.055 kg, while the result of equivalent stress the maximum value reached 0.26726 MPa. The model 1 also shows the ability to withstand the least vibration compared to the other two models.